Essential stability in set optimization. (3rd July 2022) - Karuna,; Lalitha, C. S.
ABSTRACT: The objective of the paper is to study essential stability in set optimization. Essential sets of efficient and weak efficient solution sets are introduced for a set optimization problem and essential sets are identified for both the solution sets. A characterization of essential sets is given for efficient solution sets. Finally, sufficient conditions are provided for the existence of essential sets in the image space.